Археологические исследования в районе церкви св. Константина (Мангуп): I горизонт застройки (XVI-XVIII вв.) - Герцен, А.Г.; Иванова, О.С.; Науменко, В.Е.; Смокотина, А.В. (Материалы по археологии, истории и этнографии Таврии, 2007)
В 2007 г. исполняется сорок лет со времени возобновления раскопок Мангупского городища экспедицией Таврического национального университета
им. В.И. Вернадского. Их результаты, в совокупности с данными письменных и эпиграфических источников, позволяют на сегодняшний день достаточно уверенно выделить основные периоды в истории памятника: позднеримско - ранневизантийский (III - конец VIII вв.), хазарский (конец VIII - середина IX вв.), фемный (середина IX - середина XI вв.), феодоритский (XIV - третья четверть XV вв.) и турецкий (1475 г. - конец XVIII в.) . The article opens a series of publications of the most important results of excavations in the district of St. Constantine Church in the centrai part of Mangup - the largest monument in the group of «cave towns» of the South-Western Crimea. It is here where the cultural stratifications and corresponding horizons of dwelling and household buildings reflecting ail main stages of the history of Mangup settlement from the Early Byzantine period till Turkish times were investigated step by step on one excavation area. It makes this object one of the reference ones in studying the site.